Dynamic Relationship Between Inflation and Economic Growth: A Study of Macroeconomic Vulnerability in Asean 5 - Jordan Putra Cahyono; Mohtar Rasyid (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
This study investigates the nonlinear relationship between inflation and economic growth in ASEAN-5 countries, with a focus on identifying country-specific inflation thresholds and analyzing macroeconomic resilience before and after the COVID-19 pandemic. The study aims to evaluate how inflation shocks above certain thresholds influence economic stability under dynamic global conditions. Quarterly data from 2000 to 2023 including inflation rates, real GDP growth, and lending interest rates were analyzed using Threshold Autoregressive (TAR), Panel Threshold Regression (PTR), and Vector Autoregression (VAR) models. Impulse Response Functions (IRF) and Chow tests were employed to assess dynamic interactions and structural shifts across time. Results reveal heterogeneous inflation thresholds: 0.13% (Singapore), 2.11% (Malaysia), 2.39% (Philippines), and 3.25% (Thailand), while Indonesia exhibits a volatile threshold of –1.11%, reflecting structural instability. When inflation exceeds these thresholds, real GDP declines significantly, with Indonesia showing a contraction of up to 1.2% over four quarters. Post-pandemic impacts are notably stronger, indicating reduced economic resilience. The study highlights the need for adaptive, threshold-based monetary policy tailored to each country’s structural profile. Regional policy harmonization should be reconsidered in favor of context-specific responses, including inflation-targeting frameworks, commodity price stabilization, and economic diversification to strengthen resilience amid global uncertainty.